2019
DOI: 10.1097/corr.0000000000000684
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Association Between Hospital Volume and Complications After Revision Total Joint Arthroplasty: A Large-database Study

Abstract: Background Studies of primary total joint arthroplasty (TJA) show a correlation between hospital volume and outcomes; however, the relationship of volume to outcomes in revision TJA is not well studied. Questions/purposes We therefore asked: (1) Are 90-day readmissions more likely at low-volume hospitals relative to high-volume hospitals after revision THA and TKA? (2) Are in-hospital and 90-day complications more likely at low-volume hospitals relative to high-volume hospitals after revision THA and TKA? (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 42 publications
(71 reference statements)
3
32
0
1
Order By: Relevance
“…The prevalence of revision THA and TKA have been increasing with time as primary arthroplasties that have been performed in the past decades require revision and the surgical indications for primary arthroplasties had been broadened recently. 10,14,26,32 Compared with primary arthroplasties, the revision procedure of THA or TKA requires a longer surgical time, has a longer surgical incision and results in more difficult wound healing because of the previous scar, which frequently causes SSC and consequently increases the risk of PJI. 2,4,10,18,33 Many studies have identified that the revision procedure is one of the most crucial risk factors for SSC and PJI after THA or TKA, resulting in poorer clinical outcomes, longer hospital stay, and greater economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of revision THA and TKA have been increasing with time as primary arthroplasties that have been performed in the past decades require revision and the surgical indications for primary arthroplasties had been broadened recently. 10,14,26,32 Compared with primary arthroplasties, the revision procedure of THA or TKA requires a longer surgical time, has a longer surgical incision and results in more difficult wound healing because of the previous scar, which frequently causes SSC and consequently increases the risk of PJI. 2,4,10,18,33 Many studies have identified that the revision procedure is one of the most crucial risk factors for SSC and PJI after THA or TKA, resulting in poorer clinical outcomes, longer hospital stay, and greater economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Currently revision KR in England and Wales is undertaken by a large number of surgeons performing a small number of procedures (data in press and [22]). The relationship between improved outcomes and higher surgeon and higher unit volume has been established in many areas of medicine, surgery and orthopaedics [23][24][25], and recent data has confirmed this relationship in revision hip and knee replacement [26][27][28].…”
Section: The Current Landscape Of Kr Pji In the Ukmentioning
confidence: 88%
“…In light of that, we must ask what the implications might be of such a policy, and how we might balance the benefits of this approach against its costs and harms. The authors also found that hospitals in the mid-range of volume provided rates of short-term readmissions, complications, and mortality after TJA revision that were not different from the highest-volume institutions [11]. That being so, might it be more-efficient (and less burdensome) to use both mid-and highvolume hospitals if regionalization is considered?…”
mentioning
confidence: 98%
“…We do not know if previous definitions of high-volume institutes are still accurate today, and there is the possibility that previous associations between procedure volume and outcomes are now quite different [8]. Traditional nonevidence-based quartile categories of hospitals have not captured the full extent of volume-related differences [7] [11] noted, regionalization is complicated; for example, it can burden already-strained safety-net institutions, and pose unbearable (and unaffordable) travel demands on vulnerable rural populations. In light of that, we must ask what the implications might be of such a policy, and how we might balance the benefits of this approach against its costs and harms.…”
mentioning
confidence: 99%
See 1 more Smart Citation